Green Consumerism in Environmental Learning: 7th-grade Students Pro-Environmental Behavior in Science Subject - Ilmi Zajuli Ichsan; Diana Vivanti Sigit; Mieke Miarsyah; Md. Mehadi Rahman; R. Ahmad Zaky El Islami; Husamah Husamah (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2020)
Science education in the 21st century including biology learning at the level of Junior High School requires a more contextual implementation. Environmental learning topics such as green consumerism is a contextual topic in biology learning. Students must have high Pro-Environmental Behavior (PEB) to participate in protecting the environment. The purpose of this study was to measure the PEB of students at the 7th-grade level. The research method used descriptive with survey data collection techniques. The study was conducted in November-December 2018 at State Junior High School 1 South Tambun, West Java, Indonesia. A total sample of 135 students in 7th grade was selected by simple random sampling. The results showed there were six PEB indicators based on Green Consumerism that were Energy Conservation (86.37), Transportation (56.67), Waste Avoidance (53.04), Daily Consumption (64.44), Recycling (58.89), Social Behavior (60.54). Among the six indicators, only energy conservation was categorized as very high, while the others are categorized as moderate. This study concluded that PEB students must be improved by various models, methods, and media in biology learning.Keywords: Environmental learning, green consumerism, pro-environmental behavior